THE LEVEL OF STATE CONTROL OVER THE EDUCATION SERVICES QUALITY IN THE CONTEXT OF VIEWS OF STUDENTS FROM DOMESTIC INSTITUTION OF HIGHER EDUCATION - Moroz S.A. (Theory and Practice of Public Administration, 2019)
Problem setting. Ensuring the quality of higher education is identified by the signatories of the United Nations General Assembly resolution at the level of one of the Global Goals for sustainable development of humanity. For fulfilment of the signed policy document by Ukraine in 2017, the National Report "The Objectives of Sustainable Development: Ukraine in the framework of which the authors of the Report identified the goal "Qualitative Education" due to the need to reform the educational sphere and solve the problems associated with "improving the quality of higher education and ensuring its close communication with science, assistance in the formation of educational and science cities in the country ". The fulfilment of this task cannot be imagined without the state’s participation in the relevant process. Formalization of the state’s participation in ensuring the quality of education, as well as in controlling the quality of educational activities of Institutions of higher education, on the one hand, requires determination of the level of its competence on the object of management influence, and on the other - determination of the readiness of this object to perception of such influence. Recent research and publications analysis. A significant contribution to solving the problems of public administration of the development of the higher education system was carried out by L.V. Golovij (content of the system of public administration of higher education in Ukraine was determined), N.L. Gubers`ka (was held an analysis of the peculiarities of the functioning of the main elements of the system of public administration in higher education), S.M. Dombrovs`ka (the theoretical and methodological basis for solving problems of public administration of higher education was considered), V.I. Lugovy`j (the problems of providing by state of quality of educational services were identified), S.V. Majboroda (analysis of the content of public administration of higher education in Ukraine was held ), V.M. Moroz (the place and role of education in the system of development of the state’s labour potential was determined), N.G. Protasova (the directions of reforming the higher education system of Ukraine were justified), S.O. Shevchenko (the place and role of state-public administration of higher education quality in Ukraine were defined) and other researchers. Despite the sufficient level of scientific attention to the problems of public administration in the development of the system of higher education, some of its issues still remain open to further scientific research. The paper objective – to proposed ways to improve the content and practice of usage of mechanisms of public administration of higher education quality, basing on the results of analysis of students’ point of view about state’s competence in providing control over the quality of the education activities of Institutions of higher education and quality of higher education The paper main body. 563 students took part in the survey on the determination of the students’ opinion about the necessity and the capacity of state control over the quality of educational services provision, with domestic Institutions of higher education, 542 of which filled their questionnaires correctly. For objective reasons, the survey cannot be considered as a representative one. At the same time, the results of the survey can be used as an informational and analytical basis for the processing of managerial decisions regarding the state’s influence on the system of higher education and the subsystem of its quality ensuring. Based on the analysis of respondents’ responses, we can formulate the following main generalizations. First of all, the overwhelming majority of respondents (90%) supported the idea of ​​the need for providing strict state control over the quality of educational provision by universities (70% of respondents expressed the need for strict control, but without violating the principle of so-called university autonomy; 20% of respondents are convinced that strict state control should be held without any limitations). The obtained result convincingly justifies about the existence of a sustained request from the participants of the educational process (representatives of society) to strengthen of the state’s role in the functioning of the system of ensuring with the Institutions of higher education and the quality of education activities and quality of higher education. Secondly, only 10% of respondents were convinced that the state should not strictly control the quality of educational activities of the Institutions of higher education and the quality of higher education. In general, such a result may be justified, as the historical retrospective of the formation and development of interaction between the institute of the state and the university institution testifies to the autonomy of the last one. In support of this point of view, it can be reminded that the so-called models of the Bologna and Paris Universities, which are the basis for the development of modern European universities, are solely based on student and professorial self-government. At the same time, we cannot but mention, that the overwhelming majority of domestic Institutions of higher education for objective reasons are not able to take advantage of autonomy, and therefore the realization of its potential does not seem possible. Conclusions of the research. From the side of the direct participants of the process of higher education obtaining, to be more direct students of Institutions of higher education, there is a request (expectation) to increase the role of the state in ensuring the quality of education activities and quality of higher education provided by Institution of higher education. Such readiness of one of the components of the object of managerial attention not only explains the need for institutionalization of the competence of the state as for implementation of control over the relevant subject-objective object, but also the obligation in increase of its responsibility level to society for the efficiency of the chosen procedures and activities. Satisfaction by the state of this request (expectation) can be made within the framework of improvement the content and practice of realisation the legal and regulatory mechanism of public administrations of higher education quality, for example: addition to the article 16 of the Law of Ukraine "On Higher Education" norms concerning the implementation of state control over the efficiency of the functioning of internal and external quality assurance systems; supplementing the norm of article 77 of the Law of Ukraine "On Higher Education" with the provision that state supervision (control) focuses both on subjects of the quality assurance system and on the quality of higher education.